Engaging Students in Class Research to Improve Their Learning Experience - Johnson, Hannah; Carroll, Zechariah; Omotajo, Damilola; Choudhary, Madhusudan (IJRDO-Journal of Applied Science, 2016)
Students enrolled in introductory genetics courses often arrive with a vague understanding of coregenetic principles and concepts. Specifically, the wild-type phenotype, defined as the mostcommon phenotype within a population, is often mistaken as the dominant phenotype. Presentedhere is a research-based activity that engages students in data collection and analysis whilechallenging them to eschew misconceptions concerning general principles. The protocolsdescribed here can be implemented in classrooms, teaching laboratories, or recitation sessions toelucidate these concepts across sub-disciplines such as cell biology, genetics, molecular biology,and microbiology.